Prone Hip extension muscle recruitment is associated with hamstring injury risk in amateur soccer - Schuermans, J.; Van Tiggelen, D.; Witvrouw, E. (International Journal of Sports Medicine, 2017)
`Core stability` is considered essential in rehabilitation and prevention. Particularly with respect to hamstring injury prevention, assessment and training of lumbo-pelvic control is thought to be key. However, supporting scientific evidence is lacking. To explore the importance of proximal neuromuscular function with regard to hamstring injury susceptibility, this study investigated the association between the Prone Hip Extension (PHE) muscle activation pattern and hamstring injury incidence in amateur soccer players. 60 healthy male soccer players underwent a comprehensive clinical examination, comprising a range of motion assessments and the investigation of the posterior chain muscle activation pattern during PHE. Subsequently, hamstring injury incidence was recorded prospectively throughout a 1.5-season monitoring period. Players who were injured presented a PHE activation pattern that differed significantly from those who did not. Contrary to the controls, hamstring activity onset was significantly delayed (p=0.018), resulting in a shifted activation sequence. Players were 8 times more likely to get injured if the hamstring muscles were activated after the lumbar erector spinae instead of vice versa (p=0.009). Assessment of muscle recruitment during PHE demonstrated to be useful in injury prediction, suggesting that neuromuscular coordination in the posterior chain influences hamstring injury vulnerability